Examining the Effectiveness of Augmented Reality-Based Practical Models in Electropneumatic Education in Vocational High Schools - Moch. Sukardjo; Robinson Situmorang; Annis Kandriasari; Marsofiyati; Stephanus Turibus Rahmat; Luh Putu Putrini Mahadewi (Universitas Pendidikan Ganesha, 2024)
The challenges in teaching electropneumatics in vocational high schools (SMK) lie in the limited availability of learning media that can facilitate effective and engaging practical activities. This study aims to examine the effectiveness of implementing an augmented reality-based practical model by assessing its impact on: student learning motivation, student learning outcomes, and student satisfaction. The research employed a quantitative method with data collection through tests, checklists, and questionnaires. Data were collected before and after the implementation of the model using pre-tests, post-tests, motivation checklists, and user satisfaction questionnaires. The results indicate that the application of the augmented reality-based practical model effectively increased student learning motivation from the moderate category (58.5) to the high category (76.0). Additionally, students’ learning outcomes showed significant improvement, with average pre-test scores of 54.2 and post-test scores of 77.6. To measure the improvement in student understanding, the N-Gain Score was used, showing a 31.48% increase in understanding, categorized as moderate. Student satisfaction with the application was also rated positively, though there is room for improvement. Descriptive analysis demonstrated that this model significantly enhanced students' understanding of electropneumatic material and had a positive impact on user satisfaction. In conclusion, the augmented reality-based practical model has been proven effective in improving student motivation, learning outcomes, and satisfaction.